2015
DOI: 10.1080/17429145.2014.999836
|View full text |Cite
|
Sign up to set email alerts
|

Spatial expression of the Arabidopsishydroperoxide lyasegene is controlled differently from that of theallene oxide synthasegene

Abstract: The hydroperoxide lyase (HPL) pathway for six carbon (C6) volatiles and the allene oxide synthase (AOS) pathway for jasmonates (JAs) share the first part of the pathway. To avoid competition, a separate localization of HPL and AOS might be important. A fusion protein comprising Arabidopsis HPL and green fluorescent protein was transported into chloroplasts, where AOS was located. Arabidopsis harboring β-glucuronidase (GUS) gene downstream of Arabidopsis HPL promoter (pAtHPL::GUS) showed different GUS activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
2
8
0
Order By: Relevance
“…Stumpe et al (2010) reported that JA is not present in the moss P. patens. In this study, metabolite analysis of M. polymorpha and K. flaccidum showed substantial levels of OPDA but no accumulation of JA and JA-Ile, unlike Arabidopsis and other organisms (Mwenda et al 2015). A similar result was obtained by Yamamoto et al (2015).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Stumpe et al (2010) reported that JA is not present in the moss P. patens. In this study, metabolite analysis of M. polymorpha and K. flaccidum showed substantial levels of OPDA but no accumulation of JA and JA-Ile, unlike Arabidopsis and other organisms (Mwenda et al 2015). A similar result was obtained by Yamamoto et al (2015).…”
Section: Discussionsupporting
confidence: 78%
“…The MS was used in negative ion mode and ions were detected using multiple reaction monitoring. Quantification was based on the internal standard and standard curves (Mwenda et al 2015).…”
Section: Substrate and Product Specificities Of Recombinant Mpaoss Anmentioning
confidence: 99%
“…() there are two ways to accomplish this. First, by a distinct spatiotemporal expression of HPL and AOS (Mwenda et al ., ), and, second, by expression of pathway‐specific LOXs. While some plant species possess pathway‐specific LOXs that feed 13‐HPs either into the AOS branch alone, leading to the formation of JA, or into the HPL branch, leading to the formation of GLVs (Allmann et al ., ; Christensen et al ., ), other plant species have LOXs that can supply substrate to both pathways (Wang et al ., ; Mochizuki et al ., ).…”
Section: Biosynthesismentioning
confidence: 99%
“…There are two ways to accomplish distinct regulation of each pathway. First, distinct spatiotemporal expression of the enzymes next to LOXs, i.e., HPL and AOS . Alternatively, a distinct set of LOX‐HPL and LOX‐AOS may be expressed.…”
mentioning
confidence: 99%